Socio-Economic Profile of Ornamental Fish Producers in Maharashtra State, India - Bharat Yadav; Arpita Sharma; S. N. Ojha; M. M. Shirdhankar; R. Pai (Journal of Indian Fisheries Association, 2017)
The present study was conducted to assess the socioeconomic profile of ornamental fish producers of the Maharashtra state. In the state, under the scheme 'Rainbow Revolution', started in 2007, 302 men and women have been benefited who were involved in breeding, rearing and production of ornamental fishes. The study was carried out in the districts of Thane, Mumbai, Ratnagiri, Sindhudurg and Rest of Maharashtra districts. The information was collected from 110 ornamental fish producers, of which 82 were men and 28 women. The semi-structured interview schedule was prepared to study social and economic profile. The socio-economic status indicates that the majority of the producers were males, belonging to middle-age group and predominantly of Hindu community. The status of educational analysis indicated that 52.73% producers were graduates and 31.82% higher secondary while few fisheries graduates have also taken up ornamental fish production as a self-employment. The ornamental fish producers were indicated to have medium level of social participation. The majority of the producers were having sufficient experience in ornamental fish production which indicated ornamental fish production as primary occupation. The results showed that the increase in experience in ornamental fish production, level of education and trainings attended by ornamental fish producers were positively and significantly affecting the household income of the producers. Based on the study it can be recommended that ornamental fish producers should be organized into formidable groups such as Self Help Groups (SHG'S), Farmer's Organizations (FO) and cooperative society to realize economies of scale in the purchase of inputs and marketing. Further, the socio-economic characteristics of ornamental fish producers must be taken into account for formulation, designing and success ful implementation of developmental programmes